Analysis of Consumer Demand and Preference for Rabbit Meat in Benin - ADANGUIDI, JEAN (My University, 2020)
The demand for rabbit meat exists and would only be satisfied at 50% and the holiday periods often have quite high demands. This demand is growing rapidly as it is increasingly valued by Beninese with modest incomes in search of dietary diversification and limiting cholesterol average. Rabbits are sold at a relatively high price in the Ouémé/Plateau region compared to other regions of the country, due to the higher demand there. Rabbits produced in South Benin are relatively more competitive compared to imported rabbit meat. Consumers of rabbit meat are mainly active civil servants (50% of cases) and low-income individuals. These consumers believe that locally produced rabbit is of very good quality and tastes very good.
Keywords: Rabbit demand; consumer preference; Kendall test; Benin